Pursuing green growth in Asia and the Pacific - Chung, Rae Kwon; Quah, Euston (Gale virtual reference library, 2010)
Aims to develop the new paradigm for environmentally sustainable economic growth or 'green growth' in Asia and the Pacific. Discusses the present status of environmental sustainability, especially the issue of eco-efficiency of consumption and production patterns.